THE EFFECT OF THE PROBLEM-BASED LEARNING (PBL) MODEL ON STUDENTS' CRITICAL THINKING ABILITIES IN NEWTON'S LAWS - Lulu Agustina (Contextual Natural Science Education Journal, 2025)
This study aims to analyze in depth the effect of the Problem-Based Learning (PBL) model on students’ critical thinking skills in Newton’s Laws, which is one of the fundamental topics in high school physics. Using a quasi-experimental design involving control and experimental groups, the research explores how PBL can enhance aspects of critical thinking such as analysis, evaluation, and inference. The subjects of the study were tenth-grade students from high schools in Mataram City, West Nusa Tenggara, with a total sample of 60 students evenly divided into two groups. The main instrument was a critical thinking test developed based on Facione’s (1990) indicators of critical thinking, which include information analysis, argument evaluation, and logical inference. Statistical analysis using an independent t-test showed that the group applying PBL achieved a higher average score in critical thinking skills (78.5) compared to the conventional group (65.2), with a t-value of 4.23 and p < 0.05, indicating a significant difference. The discussion emphasizes that PBL encourages students to actively identify problems, collect empirical data, and make evidence-based decisions, thereby effectively improving their critical thinking skills. The conclusion of this study states that the PBL model is proven to be more effective than conventional methods in the context of physics learning, with practical implications for broader implementation in Indonesian schools. Suggestions for future research include expanding the sample size and integrating technology to strengthen the findings.